2020
DOI: 10.4085/1062-6050-147-19
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Trainers' Competence, Education, and Perceptions Regarding Transgender Student-Athlete Patient Care

Abstract: Context Transgender student-athletes are increasingly participating in sport, requiring athletic trainer (AT) preparedness to care for their needs. Objective To measure ATs' (1) perceived definition of transgender, (2) comfort and competence working with transgender student-athletes, (3) sources of education, (4) perceived legal concerns, and (5) perception of competitive advantage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…34 In this same study, half of the respondents reported feeling comfortable caring for transgender patients, and about half felt competent in their ability to care for transgender versus cisgender patients. 34 A lack of comfortable and competent athletic trainers who can deliver high-quality, PCC to transgender patients is doing a disservice to the transgender population and the athletic training profession. 35 With this current lack of knowledge, it is imperative that the profession works not only to address credentialed athletic trainers' lack of knowledge but also current athletic training students' knowledge on transgender patient care.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…34 In this same study, half of the respondents reported feeling comfortable caring for transgender patients, and about half felt competent in their ability to care for transgender versus cisgender patients. 34 A lack of comfortable and competent athletic trainers who can deliver high-quality, PCC to transgender patients is doing a disservice to the transgender population and the athletic training profession. 35 With this current lack of knowledge, it is imperative that the profession works not only to address credentialed athletic trainers' lack of knowledge but also current athletic training students' knowledge on transgender patient care.…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, equal treatment will not suffice if the goal is to eliminate health disparities, and transgender patients face both health and health care disparities. 34 By working toward equity, athletic trainers will expand access to health care, a PCC principle. 30 In a comparison between athletic training practice and primary care, Green and Sauers 47 report successful primary care delivery outcomes, and one outcome is equity of care.…”
Section: Patient-centered Carementioning
confidence: 99%
See 3 more Smart Citations